Spinoza, Deep Ecology, and Human Diversity – Schizophrenics and Others Who Could Heal the Earth If Society Realized Eco-Literacy - MacDonald, Brenden James (The Trumpeter, 2012)
The author, who is a diagnosed schizophrenic and a student of Philosophy, explores the notion of the active love, of Spinoza and Arne Naess, in association with Fritjof Capra’s concept of Eco-Literacy and with Gregory Bateson’s ecological theory of schizophrenia. Via personal anecdotes and synthesis, the claim is made that enriching respect and understanding of our human diversity, and especially seeking the social integration of abnormal psychologies, should be a key goal of Deep Ecology-related thought and action.